Bananas, Trinidad, B.W.I. - (:unkn) unknown (Canning and Co. Ltd. Trinidad, B.W.I., 2009)
A picture of a man amists the broad leaves of the banana trees.
Colour: Coloured; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Men--Trinidad and Tobago